Editor's choice - five year outcomes of the endurant stent graft for endovascular abdominal aortic aneurysm repair in the ENGAGE registry - Teijink, Joep A. W.; Power, Adam H.; Böckler, Dittmar; Peeters, Patrick; van Sterkenburg, Steven; Bouwman, Lee H.; Verhagen, Hence J.; Bosiers, Marc; Riambau, Vincente; Becquemin, Jean-Pierre; Cuypers, Philippe; van Sambeek, Marc (European journal of vascular and endovascular surgery, 2019)
Objective/background - Endovascular abdominal aortic aneurysm repair (EVAR) is commonly used to treat abdominal aortic aneurysm (AAA). However, the incidence of long-term complications and the need for re-interventions after EVAR remain a concern. Newer generation stent grafts have encouraging short and mid-term outcomes, but thorough analysis of their long-term performance is necessary. - Methods - The ENGAGE registry includes a total of 1263 patients with AAA enrolled from March 2009 to April 2011 at 79 centres across 30 countries. The aim of this study is to present standard EVAR outcomes in the registry after five years. - Results - A significant proportion of the ENGAGE patients presented with challenging features, such as 15.2% with an AAA diameter >7 cm, 12.0% with proximal neck lengths <15 mm, and 10.2% with infrarenal neck angles >60°. Of the 1263 enrolled subjects, 17.8% were implanted outside of the instructions for use for the device. At the five year follow up, the Kaplan-Meier overall survival rate was 67.4% and the freedom from aneurysm related mortality was 97.8%. Freedom from aneurysm rupture, secondary procedures, and conversion to open repair at five years were 98.6%, 84.3%, and 97.9% respectively. The five year freedom from type IA endoleaks was 95.2% and for type III endoleaks 97.4%. Aneurysm sac diameter at five years was observed to have either decreased ≥5 mm in diameter or remained stable in 89.4% of the patients. - Conclusion - Five year follow up of patients in the ENGAGE registry demonstrates sustained safety, effectiveness, and durability in an international cohort that is reflective of real world experience. Additional follow up is expected through to 10 years.